Early versus late tube feeding initiation after PEG tube placement: Does time to feeding matter?. Issue 5 (May 2021) - Wesley, S.; Samuels, N.; Williams, K.; Danner, O.; Smith, R.; Butler, C.; Nguyen, J.; Udobi, K.; Childs, E.; Sola, R.
Highlights: Variation exists in the timing of tube feed initiation after percutaneous endoscopic gastrostomy tube placement. The aim of our study was to review outcomes of early tube feed versus late tube feed initiation after PEG tube placement. There was no difference with feeding intolerance at 12 h, 24 h, and 48 h. There was no difference when comparing post-operative complications. Early tube feeding after PEG placement is safe and equivalent to late tube feeding in the adult trauma population. Abstract: Background: Variation exists in the timing of tube feed initiation after percutaneous endoscopic gastrostomy (PEG) tube placement. The aim of our study was to review outcomes of early tube feed (ETF) versus late tube feed (LTF) initiation after PEG tube placement. Methods: We performed a retrospective review of all trauma patients who underwent PEG tube placement from 1/2014 to 12/2018. ETF was defined as initiation < 24 h and LTF > 24 h after placement. The primary outcome measure was feeding intolerance and secondary outcomes included post-operative complications. All statistical analyses were performed using standard statistical methods (e.g. Pearson's Chi-squared, Fisher's exact and Mann Whitney- U tests). Results: There were 295 patients (164 ETF and 131 LTF) that received a PEG tube at our level 1 trauma center. There was no difference with feeding intolerance at 12 h (5% vs. 4%; p  = 0.88), 24 h (1% vs. 2%; p =  1.00), and 48 h (4% vs. 4%; p =  1.00). There was no difference when comparing intolerance symptoms such as nausea and vomiting (1% vs. 2%; p =  0.79), abdominal tenderness (2% vs. 3%; p =  0.76), high gastric residuals (2% vs. 2%; p =  1.00) and aspiration (0% vs. 2%; p =  0.39). There was no difference when comparing post-operative complications (4% vs. 8%; p =  0.21). Conclusions: Early tube feeding after PEG placement is safe and equivalent to late tube feeding in the adult trauma population. Future prospective studies are warranted to establish the optimal timing for initiation of tube feeds after PEG tube placement.